(untitled) (Al-Farooq Journal of Sciences, 2026)
Complete blood count (CBC) is one of the most commonly used laboratory tests for evaluating hematological status and detecting various blood disorders . This study aimed to assess selected hematological parameters and investigate gender related differences among individuals attending Al-Qarah Bulli General Hospital. The study was conducted on 100 CBC testes, including 41 males and 59 females. Hematological parameters including RBC, WBC, HGB, PLT, HCT, MCV, MCH, and MCHC were analyzed using an automated hematology analyzer. Data were analyzed using SPSS software, and results were expressed as mean ± standard deviation (SD).Independent sample t-test was used to compare males and females, with statistical significance considered at P<0.05. The results showed significantly higher values of RBC, HGB, HCT, MCV, and MCH in males compared with females (P<0.05), while no significant differences were observed in WBC, PLT, and MCHC (P<0.05).